Human Resource Practices and Quality Assurance Among Teachers in Public Secondary Schools in the Central Region, Uganda - Anyango, Mary; Kamaduuka, Regis Zombeire; Kaahwa, Goretti (East African Journal of Interdisciplinary Studies, 2020)
The study aimed at establishing the influence of human resource practices on quality assurance among secondary school teachers in the central region of Uganda. It was guided by the objective of establishing the relationship between on-job training, off-job training, and promotions on quality assurance among teachers in the central region of Uganda. It was a desktop content review of literature journal articles and research dissertations that was thematically analysed. The findings obtained showed that to a great extent, the provision of on-job training, off-job training and promotions to teachers enhances the quality assurance in secondary schools. Thus, it was concluded that the professional development of teachers is a critical aspect that all administrators should not neglect. Consequently, it was recommended that junior teachers should be assigned to senior teachers who should act as coaches, supervisors and mentors. Also, off-job training policies should be developed to enhance teachers’ teaching skills and once trained; the teachers have to be promoted.